2021
DOI: 10.3389/fcell.2021.646754
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Development of the Hermaphroditic Scallop Argopecten irradians Revealed by Morphological, Endocrine and Molecular Analysis

Abstract: Simultaneous or functional hermaphrodites possessing both ovary and testis at the same time are good materials for studying sexual development. However, previous research on sex determination and differentiation was mainly conducted in gonochoristic species and studies on simultaneous hermaphrodites are still limited. In this study, we conducted a combined morphological, endocrine and molecular study on the gonadal development of a hermaphroditic scallop Argopecten irradians aged 2–10 month old. Morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 56 publications
3
9
1
Order By: Relevance
“…For example, Li et al (2016) showed that PyDMRT was testis-biased, and Li et al (2018) suggested that the My|XP_021353714.1 (previously known as Dmrt1L) is a yang gene for determining the timing of sex differentiation in M. yessoensis [ 46 ]. Similar results were also found in Argopecten irradians [ 11 ], in which Dmrt1L showed male-biased expression in the gonad. In particular, the current study showed that the gene (Ap|evm.model.scaffold_235.403) from the hermaphrodite scallop A. purpuratus is also expressed specifically in the testis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For example, Li et al (2016) showed that PyDMRT was testis-biased, and Li et al (2018) suggested that the My|XP_021353714.1 (previously known as Dmrt1L) is a yang gene for determining the timing of sex differentiation in M. yessoensis [ 46 ]. Similar results were also found in Argopecten irradians [ 11 ], in which Dmrt1L showed male-biased expression in the gonad. In particular, the current study showed that the gene (Ap|evm.model.scaffold_235.403) from the hermaphrodite scallop A. purpuratus is also expressed specifically in the testis.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have demonstrated that the Dmrt gene is associated with sex determination/differentiation in bivalves. For example, Dmrt is significantly differentially expressed between the ovaries and testes of scallops [ 11 , 12 ], and RNAi of Dmrt can lead to the failure of gonadal differentiation in oysters [ 13 ]. However, many questions about the Dmrt gene in bivalves remain to be answered.…”
Section: Introductionmentioning
confidence: 99%
“…On day 50, both genes were significantly higher in the 11 and 16 °C groups compared to the 21 °C group. Considering that FoxL2 and Dmrt1L are distributed in germ cells and follicle cells in scallops (Li et al, 2018;Liu et al, 2012;Wei et al, 2021), the results indicate that proportion of these two types of cells increased after 50 days of treatment, especially for the 11 °C and 16 °C groups, consistent with the histological observations (Figure 3). LOG10 (Dmrt1L/FoxL2) was used to distinguish differentiated from undifferentiated samples, with values below 0 for ovary and values higher than two for testis (Li et al, 2018).…”
Section: Effect Of Temperature On the Expression Of Foxl2 And Dmrt1l In The Gonadssupporting
confidence: 85%
“…For example, in Phylum Mollusca, Class Bivalvia, there are gonochoric species with genetic sex determination in the absence of heteromorphic chromosomes and hermaphroditic species in which male and female gonadal material are present in the same individual, either simultaneously (e.g., bay scallop, Argopecten irradians ) or sequentially (Breton et al, 2018; Wei et al, 2021). A recent comparative phylogenomic survey of sex in the family Pectinidae suggests that sex chromosome homomorphy in gonochoric scallop species evolved as early as 350 million years ago via repetitive element‐driven chromosomal rearrangement and has been maintained through regulatory flexibility of sex‐related genes during gonadal development (Han et al, 2022).…”
Section: Introductionmentioning
confidence: 99%